Eating habits of a population undergoing a rapid dietary transition: portion sizes of traditional and non-traditional foods and beverages consumed by Inuit adults in Nunavut, Canada - Sheehy, Tony (BioMed Central, 2013)
BACKGROUND: To determine the portion sizes of traditional and non-traditional foods being consumed by Inuit adults in three remote communities in Nunavut, Canada. METHODS: A cross-sectional study was carried out between June and October, 2008. Trained field workers collected dietary data using a culturally appropriate, validated quantitative food frequency questionnaire (QFFQ) developed specifically for the study population. RESULTS: Caribou, muktuk (whale blubber and skin) and Arctic char (salmon family), were the most commonly consumed traditional foods; mean portion sizes for traditional foods ranged from 10 g for fermented seal fat to 424 g for fried caribou. Fried bannock and white bread were consumed by >85% of participants; mean portion sizes for these foods were 189 g and 70 g, respectively. Sugar-sweetened beverages and energy-dense, nutrient-poor foods were also widely consumed. Mean portion sizes for regular pop and sweetened juices with added sugar were 663 g and 572 g, respectively. Mean portion sizes for potato chips, pilot biscuits, cakes, chocolate and cookies were 59 g, 59 g, 106 g, 59 g, and 46 g, respectively. CONCLUSIONS: The present study provides further evidence of the nutrition transition that is occurring among Inuit in the Canadian Arctic. It also highlights a number of foods and beverages that could be targeted in future nutritional intervention programs aimed at obesity and diet-related chronic disease prevention in these and other Inuit communities.